Investigational Approaches for Mesothelioma - Surmont, Veerle F.; van Thiel, Eric R.; Vermaelen, Karim; Van Meerbeeck, Jan P. (Frontiers in Oncology, 2011)
MPM is a rare, aggressive tumour with a poor prognosis. In view of the poor survival benefit from first-line chemotherapy and the lack of subsequent effective treatment options, there is a strong need for the development of more effective treatment approaches for patients with MPM. This review will provide a comprehensive state of the art of new investigational approaches for mesothelioma. In an introductory section, the aetiology, epidemiology, natural history and standard of care treatment for MPM will be discussed. This review provide an update of the major clinical trials that impact mesothelioma treatment, discuss the impact of novel therapeutics and provide perspective on where the clinical research in mesothelioma is moving. The evidence was collected by a systematic analysis of the literature (2000–2011) using the databases Medline (National Library of Medicine, USA), Embase (Elsevier, Netherlands), Cochrane Library (Great Britain), National Guideline Clearinghouse (USA), HTA Database (International Network of Agencies for Health Technology Assessment – INAHTA), NIH database (USA), International Pleural Mesothelioma Program – WHOLIS (WHO Database) , with the following keywords and filters: mesothelioma, guidelines, treatment, surgery, chemotherapy, radiotherapy, review, investigational, drugs Currently different targeted therapies and biologicals are under investigation for MPM. It is important that the molecular biologic research should first focus on mesothelioma-specific pathways and biomarkers in order to have more effective treatment options for this disease. The use of array technology will be certainly an implicit gain in the identification of new potential prognostic or biomarkers or important pathways in the MPM pathogenesis. Probably a central mesothelioma virtual tissue bank may contribute to the ultimate goal to identify druggable targets and to develop personalized treatment for the MPM patients.